PERILAKU ASERTIF PADA REMAJA - Eni Rohyati dan Yusna Hanung Purwandari (Jurnal Psikologi, 2015)
Youth life that usually rely on peers and also being demanded to be independent and assertive, are certainly confusing for adolescence. Comparing to adult, peer is the most important influence for adolescence. Therefore, to be assertive and independent to have opinion is a risky for teens. This preliminary research aim is to investigate the internal and external factors attributing the assertive behavior on a subject. This research is unique since the subject lives in a dormitory, and therefore she has complex problems i.e. adaptation for new environment, home sick, and peer demanding on conformity. The research revealed that the subject relies more on her peer than to her parents. She tends to be non assertive and low self-esteem. Suggestion for the next research is discussed.